DEVELOPING CREATIVE SKILLS IN CHILDREN THROUGH WORKING WITH NATURAL MATERIALS (International Congress on Economics, Management and Business Studies, 2026)
This article examines the pedagogical importance of developing creative skills in children through working with natural materials. Natural materials are considered an effective means of developing children’s imagination, independent thinking, aesthetic taste, fine motor skills, observation, and diligence. Practical activities with leaves, branches, seeds, stones, sand, shells, cotton, straw, dried flowers, and other natural objects help children understand nature, appreciate its beauty, and develop a careful attitude toward the environment. The article analyzes the educational and developmental potential of activities based on natural materials, their role in shaping children’s creativity, and the methodological approaches of teachers. It also highlights ways of developing ecological culture, imagination, creative thinking, and practical activity skills in children through work with natural materials.
Keywords: natural materials, creative skills, children’s creativity, preschool education, aesthetic education, ecological education, handicraft, imagination, fine motor skills, practical activity.